Breast MRI at 7 Tesla with a bilateral coil and robust fat suppression. Issue 3 (7th October 2013) - Brown, Ryan; Storey, Pippa; Geppert, Christian; McGorty, KellyAnne; Klautau Leite, Ana Paula; Babb, James; Sodickson, Daniel K.; Wiggins, Graham C.; Moy, Linda
Abstract : Purpose: To develop a bilateral coil and fat suppressed T1‐weighted sequence for 7 Tesla (T) breast MRI. Materials and Methods: A dual‐solenoid coil and three‐dimensional (3D) T1w gradient echo sequence with B1 + insensitive fat suppression (FS) were developed. T1w FS image quality was characterized through image uniformity and fat–water contrast measurements in 11 subjects. Signal‐to‐noise ratio (SNR) and flip angle maps were acquired to assess the coil performance. Bilateral contrast‐enhanced and unilateral high resolution (0.6 mm isotropic, 6.5 min acquisition time) imaging highlighted the 7T SNR advantage. Results: Reliable and effective FS and high image quality was observed in all subjects at 7T, indicating that the custom coil and pulse sequence were insensitive to high‐field obstacles such as variable tissue loading. 7T and 3T image uniformity was similar ( P  = 0.24), indicating adequate 7T B1 + uniformity. High 7T SNR and fat–water contrast enabled 0.6 mm isotropic imaging and visualization of a high level of fibroglandular tissue detail. Conclusion: 7T T1w FS bilateral breast imaging is feasible with a custom radiofrequency (RF) coil and pulse sequence. Similar image uniformity was achieved at 7T and 3T, despite different RF field behavior and variable coil–tissue interaction due to anatomic differences that might be expected to alter magnetic field patterns.J. Magn. Reson. Imaging 2014;39:540–549 . ©2013 Wiley Periodicals, Inc.